Medium-Term No-Tillage, Additional Compaction, and Chiseling as Affecting Clayey Subtropical Soil Physical Properties and Yield of Corn, Soybean and Wheat Crops - Suzuki, Luis Eduardo Akiyoshi Sanches; Reinert, Dalvan José; Alves, Marlene Cristina [UNESP]; Reichert, José Miguel (MDPI, 2022)
Understanding the soil-plant relationship is important to determine critical limits of soil properties that influence crop growth and yield. The objectives were to quantify the influence of soil compaction levels on physical properties and crop growth and yield in a clayey Oxisol. An experiment was performed having in the main plots, levels of soil compaction (NT: no-tillage during six years, NTC: NT + four passes of a 10 Mg machine in the agricultural year 2003/2004, and Chisel: NT + chiseling and harrowing in the agricultural year 2003/2004), and in the sub-plots, the summer crops soybean and corn, and wheat in the winter season. We measured soil physical and mechanical properties, along with yield of corn, soybean and wheat, and root growth of that last two crops. After four passes of a 10 Mg machine, the soil resistance to penetration increased to a 0.12 m depth, while Chisel disrupted the 0–0.20 m soil layer, with the effects persisting for at least nine months. Soil compaction in no-tillage concentrated in the 0.05–0.15 m layer. Corn yield was similar among the treatments, soybean yield was highest in NT, and the highest yield of wheat was in the sequence with soybean under NT.
Keywords: additional compaction; chiseling; compression index; cost of soil compaction; critical limits of soil properties; no-tillage; precompression stress